ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PERATAAN LABA - Theresia Dian (Magister Akuntansi, Universitas Atma Jaya Makassar, 2018)
This study is an empirical research that aims to determine the effect of profitability, leverage, company size, CEO's gender, CEO's educational background and CEO's level of education against income smoothing practice. The population in this study are all manufacturing companies that have been going public and listed on the Indonesia Stock Exchange (BEI) in 2014-2016. Sampling technique conducted by the author is to use purposive sampling. This study uses secondary data derived from company financial statements, company annual reports, and fact book. Total research data amounted to 134, of which 84 companies are doing income smoothing. Hypothesis testing is done by using logistic regression analysis with significance level (α) 5%. Data processing using IBM SPSS software version 22.00. The results show that profitability and leverage variables have a significant negative effect on the practice of income smoothing, while the gender variable CEO has a significant positive influence on the practice of income smoothing. Meanwhile, firm size variables, CEO education background and CEO education level have no influence on the practice of income smoothing.